Treatment of erosive lichen planus with diode laser: A case report - Sreekumar Rinku; Daryani Deepak; M P Uthkal; Shabil Muhamed Mustafa (Wolters Kluwer Medknow Publications, 2023)
Oral lichen planus (OLP) is a mucocutaneous disease. Various treatment methods have been used in the past; however, a complete cure of OLP still remains an enigma. This case report highlights low-level laser therapy (LLLT) as a treatment option with minimum side effects. The outcomes of the treatment results in this case also suggest against the simultaneous use of LLLT with corticosteroids.